PENGARUH FAKTOR FUNDAMENTAL TERHADAP PENILAIAN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muthia Harnida (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
The approaches of stock valuation can be used by the investor using the approaches of present value and price earnings ratio. This research is to investigate the effect of fundamental analysis on the stock valuation using the approach of price earnings ratio. The fundamental factor uses some variables such as dividend yield, return on assets, leverage, firm size and growth of earnings per share. The sample is manufacturing companies listed in Indonesian Stock exchange for the period of financial report of 2013 until 2015. The result indicates that statistically dividend yields, leverage, firm size, and return on assets have significant effect on the stock valuation of price earnings ratio, but growth of earnings per share does not affect the stock valuation.